Els marcadors pragmàtics compostos en el relat oral anglès i català - González, Montserrat (Caplletra. Revista Internacional de Filologia, 2001)
Pragmatic markers are linguistic units that the speaker uses to organize, recover, reformulate and segment the information thats/he supplies to the hearer. They are a feature of oral rather than written discourse. They have little or no propositional meaning. Bymeans of pragmatic markers, the speaker transmits intentions, actions, and thoughts. They help to make a text coherent in as much as they are cues that facilitate the cognitive processing of information and constrain inferences and presuppositions. They aremultifunctional, operating at several discourse levels simultaneously: sequential, rhetorical and ideational (Redeker 1990). Their omission involves a violation of gricean cooperative principle, and the maxims of quantity and relevance in particular. The pairing of two or more pragmatic markers results into a compound pragmatic marker (CPM). These units facilitate, to a great extent, the shifts onto distinct contextual realms or discourse structures (ideational, sequential and rhetorical). Their combinatory functions result into a) a change of attentional state of the speaker or shift of cognitive frame, and b) a remarkable emphasis on the illocutionary point of the segment. When a CPM is used, the processing cost of information is lowered.